2012
DOI: 10.1002/ange.201200728
|View full text |Cite
|
Sign up to set email alerts
|

Direct Investigation of Covalently Bound Chlorine in Organic Compounds by Solid‐State 35Cl NMR Spectroscopy and Exact Spectral Line‐Shape Simulations

Abstract: 35/37 Cl NMR spectroscopy studies of organic systems are very rare, with only a few neat liquids having been studied. [1] The lack of chlorine NMR spectroscopy data may be explained by the fact that 35 Cl and 37 Cl are quadrupolar (spin I = 3/2) and low-frequency isotopes. The quadrupole moments of the chlorine nuclei couple with the electric field gradient (EFG) tensor at the nuclei; this phenomenon is known as the quadrupolar interaction (QI). The quadrupolar coupling constant, C Q , and the quadrupolar asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…We conducted spectral simulations utilizing both WSolids and QUEST, and found that there were no substantial differences between the spectra generated by each method. This is likely because even the largest C Q magnitudes reported herein are substantially smaller than those observed by Perras et al [48] For example, the 35 Cl SSNMR spectrum of 12 was simulated with both programs, and resulting quadrupolar parameters were identical (within uncertainties, Figure S11), thereby confirming the validity of the simulations completed using WSolids. 35 Cl T 2 measurements and spectral intensity distributions: Many of the CT powder patterns observed in the 35 Cl SSNMR spectra obtained for complexes 1-14 have intensity distributions that do not match precisely with analytical simulations.…”
Section: Wwwchemeurjorgsupporting
confidence: 71%
See 2 more Smart Citations
“…We conducted spectral simulations utilizing both WSolids and QUEST, and found that there were no substantial differences between the spectra generated by each method. This is likely because even the largest C Q magnitudes reported herein are substantially smaller than those observed by Perras et al [48] For example, the 35 Cl SSNMR spectrum of 12 was simulated with both programs, and resulting quadrupolar parameters were identical (within uncertainties, Figure S11), thereby confirming the validity of the simulations completed using WSolids. 35 Cl T 2 measurements and spectral intensity distributions: Many of the CT powder patterns observed in the 35 Cl SSNMR spectra obtained for complexes 1-14 have intensity distributions that do not match precisely with analytical simulations.…”
Section: Wwwchemeurjorgsupporting
confidence: 71%
“…All analytical simulations shown thus far were completed using second-order perturbation theory under the high-field approximation (i.e., n 0 @ n Q , and a pure Zeeman basis set is used). Perras et al [48] recently demonstrated that the high field approximation can fail, and that the low frequency regions of 35 Cl SSNMR spectra acquired at 21.1 T (n 0 = 88.2 MHz) for a series of organochlorine compounds were not simulated correctly using perturbation theory. In this work, the values of C Q for covalently bound chlorine atoms are on the order of 70 MHz (i.e., n Q = 35 MHz).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…The satellite transitions were included in the simulations, with the area corresponding to the central transitions filled in with color. Much like the case in Figure A, the line widths of the central transition of 35/37 Cl ( Q ( 35 Cl) = −81.65(80) mb, Q ( 37 Cl) = −64.35(64) mb) covalently bonded to carbon are manageable by SSNMR and also provide information on the chemical shift. As is immediately apparent however, the line widths of the central transitions of 79/81 Br ( Q ( 79 Br) = 313(3) mb, Q ( 81 Br) = 262(3) mb), and 127 I ( Q ( 127 I) = −696(12) mb) covalently bonded to carbon become prohibitively large, spanning hundreds of MHz.…”
Section: Further Practicalities Limitations and Experimental Challementioning
confidence: 86%
“…13 As the static magnetic field strength of commercially available instruments increases, allowing faster acquisition of broad quadrupolar powder patterns, and as broadband pulse sequences are developed, 58 the acquisition of solid-state NMR spectra that fall outside of the high-field regime is becoming more practical. Recent examples of very broad quadrupolar powder patterns in solids, which were all acquired at B 0 = 21.14 T, include the 127 I NMR spectrum of SrI 2 , with a breadth of approximately 10 MHz, 59 61 Finally, a recent study we have conducted features the 121 Sb NMR spectrum of solid Ph 4 SbBr, whose central transition spans 5.5 MHz with a C Q ( 121 Sb) value of 159 MHz (ν 0 ( 121 Sb) = 215.4 MHz). 27 Note that the breadth of a quadrupolar powder pattern at a specific magnetic field strength depends not only on the magnitude of the quadrupolar interaction (i.e., values of C Q and η), but also on the spin number of the nucleus, with the total width of the powder pattern decreasing for increasing values of I.…”
Section: ■ Backgroundmentioning
confidence: 99%